CO2/H-2 methanation over M*/Mn/Fe-Al2O3 (M*: Pd, Rh, and Ru) catalysts in natural gas; optimization by response surface methodology-central composite design - Ab. Halim, Ahmad Zamani (Springer Link, 2015)
The selective catalytic of carbon dioxide (CO2) methanation with hydrogen (H2) over M/Mn/Fe-Al2O3 (M = Pd, Rh, & Ru) oxide catalysts in natural gas was investigated. Among them, Ru/Mn/Fe-Al2O3 catalyst was found to be the most potential catalyst based on activity. The optimization ratio of Ru, calcination temperature, and catalyst weight loading to improve the efficiency of CO2 conversion was studied. The results indicated that the Ru/Mn/Fe-Al2O3 catalyst ratio (5:35:60), which was calcined at 1,000 °C, was the best catalyst for CO2 conversion (96.1 %) and CH4 formation (66.0 %) at reaction temperature at 270 °C. Response surface methodology (RSM) involving central composite design (CCD) was employed to optimize Ru/Mn/Fe-Al2O3 and activity parameters (Ru loading, calcination temperature, and catalyst loading) in CO2 methanation. Under CCD, the model indicated that Ru loading was the most significant effective factor, followed by calcination temperature and catalyst loading. The optimum condition for maximum CO2 conversion was estimated at 5.5 wt % Ru loading, calcination temperature of 1,010 °C, and catalyst loading of 5 g. Under these conditions, experimental CO2 conversion efficiency was 95.0 %, which was close with the predicted value of 96.6 %. Graphical Abstract